Ethics and akhlaq of special needs kids: intellectual disabilities - Jaffer, Usman; Che Mohd Nassir, Che Mohd Nasril; Ahmed, Mohamed Ayaaz; Ahmad H.Osman, Rahmah; Mohd Darwis, Nur Hidayati; Mohamad Yusaini, Nur Syaqirah Natasha; Rusli, Siti Sarah; Zul Alam, Siti Zulaikha; Yusof, Muhammad Afiq Ikmal; Shahrul, Ilhan Syahmi (Global Academic Excellence, 2023)
This study aims to assess akhlaq and fiqh in terms of social skills and fundamental knowledge by examining the behavioral aspects of interactions among teachers and classmates. The research utilizes the Piagetian method, teacher evaluations, and self-evaluations by children. Due to the limitations in understanding assignments among the children, their responses to activities are crucial for evaluation. Teacher assessments play a key role, given their familiarity with the students. The study, involving 15 students, reveals a positive understanding of ethics and akhlaq concepts.